Increasing the efficiency of heat energy transportation - Struchaiev, Mykola; Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Postol, Yuliia; Постол, Юлія Олександрівна; Постол, Юлия Александровна (My University, 2020)
The annual global losses in the transportation of thermal energy are more than 10–20%, and in some regions up to 40% [1]. Development thermal insulation methods for pipelines vary depending on the type of installation, as operating conditions impose special requirements. A significant part of the heating mains has an air gasket [2,3,4]. Therefore, the search for ways to increase the efficiency of using heat insulation plays an important role, since it allows for a long time to reduce heat loss.
Keywords: pipeline; heat energy; transportation